Connotative Meaning Used in Maroon 5 Selected Songs “Red Pill Blues” Album - Ihsan Risyad Fadilah Putra; I Made Rajeg; I Nyoman Aryawibawa (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Every song has an important meaning that the singer intends to communicate to the audience. To have a thorough understanding of the music you wish to express, you might delve into its connotative meaning. The aims of this study were to identify the types of connotative meaning from the lyrics in selected song albums by Maroon 5 “Red Pill Blues”. The data were analyzed uses descriptive qualitative method based on the theory proposed by Leech (1974). This study found 25 data, based on the theory used there are three categorize of connotative meaning from the data above namely; positive connotative, negative connotative and neutral connotative with positive connotation as a highest occurrence. The finding show that connotative meaning is becoming increasingly. Common and maybe as a suitable learning medium. This research will provide learning with deep understanding about the meaning of the word.